Daya Saing Ekspor Crude Palm Oil dan Refined Palm Oil Asal Indonesia dan Malaysia di Pasar India - Zainuddin Zainuddin (Universitas Batangahari Jambi, 2022)
This research examines: 1) to what extent is the competitiveness of Indonesian palm oil, especially CPO and RPO in the Indian market compared to similar products from Malaysia; and 2) what factors determine the competitiveness of Indonesian CPO and RPO exports in the Indian market. The research method uses the RCA and RSCA indices as well as the regression function to determine the dominant factors that affect the competitiveness of Indonesian CPO and RPO exports in the Indian market with data ranging from 1995 to 2021. The competitiveness of Indonesian CPO exports in the Indian market shows a more stable trend in the period 1996 to 2021 and the competitiveness of Malaysian CPO in that period has decreased slowly. The competitiveness of Indonesian and Malaysian RPO exports in the Indian market decreased in the Indian market from 1996 to 2013, then there was a strengthening of competitiveness from 2014 to 2019. The competitiveness of Indonesian CPO exports to the Indian market is influenced by the volume of Malaysian CPO exports to India, the Indonesian CPO export tax, the CPO import tax in India, the real exchange rate of the Rupiah against the US Dollar, and the real price of CPO on the world market. Furthermore, the competitiveness of Indonesian RPO exports in the Indian market is influenced by the volume of Malaysian RPO exports to India, the real exchange rate of the Rupiah against the US Dollar, the export price of RPO, the price of soybean oil on the world market, and the RPO import tax in India.